Application of Rewarding Techniques and Low Impact Aerobic Exercise Activity Therapy on Hearing Hallucination Patients in the Cigeureung Public Health Center Area, Tasikmalaya City - Asep Riyana; Damara, Doni; Kustiawan, Ridwan (Asy-Syifa : Journal of Science and Technology Nursing, 2025)
Purpose:The purpose of this case study is to describe the nursing process stages, the application of reprimanding techniques and low-impact aerobic exercise therapy, the changes in signs and symptoms, and the gaps in nursing care for patients with auditory hallucinations. Methods:This study employed a qualitative design using a case study approach involving two patients diagnosed with schizophrenia experiencing auditory hallucinations. The interventions consisted of reprimanding technique therapy and low-impact aerobic exercise therapy, implemented once daily for 30 minutes over five consecutive days. Results:The results demonstrated a significant reduction in the signs and symptoms of auditory hallucinations in both patients. Patient 1 showed a decrease from 10 to 2 hallucination symptoms, while Patient 2 experienced a reduction from 11 to 4 symptoms after the intervention. Conclusions: The application of reprimanding techniques combined with low-impact aerobic exercise therapy is proven to be effective in reducing the signs and symptoms of auditory hallucinations. It is recommended that patients and families consistently apply these non-pharmacological therapies while enhancing motivation and support to help control hallucinations effectively.